A novel octa-nuclear 32-membered zirconocene macrocycle based on the aromatic selenite. Issue 2 (14th December 2016) - Yao, Nian-Tao; Zhang, Ru-Fen; Zhang, Shao-Liang; Li, Qian-Li; Ma, Chun-Lin
Abstract : A novel macrocyclic zirconocene(iv ) aromatic selenite [(CpZr)8 L16 ]·2(Cp4 Zr2 (μ-O)Cl2 ) (complex1 ) (Cp = cyclopentadienyl anion; L = 4-fluorobenzeneseleninic acid) was prepared by the reaction of bis(cyclopentadienyl)zirconium dichloride with 4-fluorobenzeneseleninic acid and characterized by elemental analysis, infrared spectroscopy, 1 H, 13 C NMR spectroscopy, ESI-MS, XRD and X-ray diffraction. Abstract : A novel macrocyclic zirconocene(iv ) aromatic selenite [(CpZr)8 L16 ]·2(Cp4 Zr2 (μ-O)Cl2 ) (complex1 ) (Cp = cyclopentadienyl anion; L = 4-fluorobenzeneseleninic acid) was prepared by the reaction of bis(cyclopentadienyl)zirconium dichloride with 4-fluorobenzeneseleninic acid and characterized by elemental analysis, infrared spectroscopy, 1 H, 13 C NMR spectroscopy, ESI-MS, XRD and X-ray diffraction. The structure analysis shows that complex1 is a centrosymmetric 32-membered macrocycle containing an eight-nuclear zirconocene. In this complex, the 4-fluorobenzeneseleninic acid ligands adopt bidentate mode in coordinating to zirconium, which play a bridging role in the formation of a macrocycle. The title compound is a rare example of aromatic selenic acid-based zirconocene derivatives. Furthermore, the preliminary in vitro anti-tumor activity of complex1 has also been studied toward breast cancer cell lines (MDA-MB-231) and human cervix cell lines (HeLa). The results indicate that complex1 shows higher activity compared with the ligand and bis(cyclopentadienyl)zirconium dichloride.